Karya Sastra Ulama Sufi Aceh Hamzah Fansuri: Bingkai Sejarah Dunia Pendidikan - Nuraini H. A. Mannan (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2016)
The Islamic literature in Indonesia designated Shaykh Hamza Fansuri as the first person to introduce poems in the form of literature in the 16th century. The phrases he introduced increased the community awareness. He was sensitive to the changes around, careful in criticizing various social problems, and creative in contributing ideas pertaining public awareness and its alternative solution. The existence of literature world is degrading due to instrumental, modern phenomena and lifestyle. Literature has increasingly lost its critical substances in capturing the universal message enclosed in existing realities. This paper suggests that the literary work should be a driving force in realizing the process of developing sound human beings. A meaningful approach to literary studies exhibits a great value in the use of the language and arrangement of words. However, aesthetic assessment in a certain language lies not in its elements but in the integrity across its elements; coherence (in the logical sense), maturity (in the psychological sense), truth, experience, and aesthetics. It is in this context that the role of literature together with human values it embedded need to be re-raised and re-promoted to foster an intact personality balancing science, morality, and art. Literature should incorporate the guidance of the human personality to the delicate, humane and cultured (humanized) soul and establish the human right values.